Stalingrad - Beevor, Antony, 1946- (New York : Viking, 1998)
On August 23, 1942, Hitler's 16th Panzer Division halted on the banks of the Volga. To their right, the city of Stalingrad blazed from the first of General von Richthofen's air raids, which ultimately killed 40,000 civilians. Many German soldiers thought the war against Russia was won. But in Stalin's namesake city on the Volga, Hitler had chosen the wrong target. The battle of Stalingrad would be the most pitiless, and perhaps the most important, battle in history. When the fighting was over, the world would begin to believe for the first time that Hitler could be defeated.
'The World Will Hold its Breath!' -- Barbarossa Relaunched -- 'The Fateful City' -- Zhukov's Trap -- The Subjugation of the Sixth Army -- German and Soviet Orders of Battle, 19 November 1942 -- The Statistical Debate: Sixth Army Strength in the Kessel.
Includes bibliographical references (pages 477-485) and index.
Keywords: 1942-1943; Stalingrad, Battle of, Volgograd, Russia, 1942-1943.; World War, 1939-1945 -- Campaigns -- Russia (Federation) -- Volgograd